Advanced distributed management of roads with driverless cars - Sapaty, P.S. (Математичні машини і системи, 2017)
The widely expected use of autonomous cars can change the landscape for car manufacturers who can rethink business models. But driverless cars may remain just toys for a long time, because the main, and extremely complex, problem may be the effective automatic management of roads with numerous driverless cars. We will try to shed some light on the real management of complex road networks with autonomous cars using high-level networking technology already tested on many applications, both civil and military. Along with optimisation on the infrastructure level, solutions will be shown for local problems by distributed emergency scenarios dynamically covering arbitrary regions with any number of communicating vehicles. Each solution will be presented and explained in a special high-level language which can be effectively interpreted in a fully distributed mode, without any central resources, and with high mobility of extremely compact scenario code. Part of this material has been accepted for presentation at The Future of Transportation World Conference in Cologne (Germany) July 5–6, 2017.